Gastric peroral endoscopic myotomy versus botulinum toxin injection for the treatment of refractory gastroparesis: results of a double-blind randomized controlled study - Gonzalez, Jean-Michel; Mion, François; Pioche, Mathieu; Garbay, Victor; Baumstarck, Karine; Boucekine, Mohamed; Debourdeau, Antoine; Rivory, Jérôme; Barthet, Marc; Vitton, Véronique (Endoscopy, 2024)
Introduction Gastric peroral endoscopic myotomy (G-POEM) is a promising technique for treating refractory gastroparesis. We present the first double-blind randomized study comparing the clinical efficacy of G-POEM versus pyloric botulinum toxin injection (BTI).Methods This randomized study, conducted in two expert centers, enrolled patients with refractory gastroparesis, medically managed for >6 months and confirmed by gastric emptying scintigraphy (GES), into two groups, G-POEM versus BTI, with follow-up of 1 year. The primary end point was the 3-month clinical efficacy, defined as a >1-point decrease in the mean Gastroparesis Cardinal Symptom Index (GCSI) score. Secondary end points were: 1-year efficacy, GES evolution, adverse events, and quality of life.Results 40 patients (22 women; mean age 48.1 [SD 17.4]), with mean symptom duration of 5.8 (SD 5.7) years, were randomized. Etiologies included idiopathic (n=18), diabetes (n=11), postoperative (n=6), and mixed (n=4). G-POEM showed a higher 3-month clinical success than BTI (65% vs. 40%, respectively; P=0.10), along with non-significantly higher 1-year clinical success (60% vs. 40%, respectively) on intention-to-treat analysis. The GCSI decreased in both groups at 3 months and 1 year. Only three minor adverse events occurred in the G-POEM group. The GES improvement rate was 72% in the G-POEM group versus 50% in the BTI group (non-significant).Conclusion G-POEM seems to have a higher clinically relevant success rate than BTI, but this was not statistically demonstrated. This study confirms the interest in treatments targeting the pylorus, either mechanically or chemically, for managing refractory gastroparesis.